Tingkat Pengetahuan Peraturan Permainan Rugby Union Ukm Rugby Universitas Negeri Surabaya 2023 - Satria Wiradika; Purbodjati Purbodjati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The goal of this study is to learn what some of the many Rugby players at Universitas Negeri Surabaya know about the rules game in 2023. This essay is really scriptural. The survey was conducted using wrong and correct tes to gather data with share the draft. 41 athlete UKM Rugby are the subjects of the essay Data is available from 3 April - 5 April 2023. Deskriptif quantitative analysis is used in data analysis technique and is disclosed in persentace form. The results show the members of the team fall into the following categories: very high sebesar 0%, high sebesar 9,8%, medium 36,6%, low 48,8%, and very low 4,9%. The aforementioned study's findings suggest that the members of the University of Negeri Surabaya's rugby team need to be more motivated to train and learn with discipline and grit. In addition, Rugby University of Negeri Surabaya instructors must provide theoretical material to improve players' cognitive awareness, particularly that of new players, It is highly recommended for all students and supporters of the University of Negeri Surabaya to support the team's rugby team to the very end so that they can achieve higher standards of performance in the future and enhance the university's reputation.